The Application of Multifunctional Endoscope Transport Carts in Bedside Endoscopy in Intensive Care Unit Patients - Zhang M; Du J; Zhang Q; Qiao F; Ye L; Hu B; Tao S (Risk Management and Healthcare Policy)
Miao Zhang,1,2,* Jiang Du,1,2,* Qiongying Zhang,1,2 Fu Qiao,3 Liansong Ye,1,4 Bing Hu,1,4 Siyuan Tao3 1Department of Gastroenterology and Hepatology, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2West China School of Nursing, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Department of Infection Control, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 4Digestive Endoscopy Medical Engineering Research Laboratory, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiongying Zhang, Department of Gastroenterology and Hepatology, West China Hospital, Sichuan University, No. 37 Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Email hxnjzqy@163.com Fu Qiao, Department of Infection Control, West China Hospital, Sichuan University, No. 37 Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Email qiaofu2005@scu.edu.cnBackground: This study aimed to investigate whether the application of multifunctional endoscope transport carts, in bedside endoscopy in intensive care unit (ICU) patients, can improve the cleaning quality of the endoscopes.Methods: A total of 175 endoscopes, used for bedside endoscopy in ICU patients in a hospital in China during November 2023 to January 2024, were randomly classified into the control group (n=88) and the experimental group (n=87). Multifunctional transport carts were used to deliver the endoscopes in the experimental group and traditionally used transport trolleys were used in the control group. Adenosine triphosphate (ATP) tests were performed to measure the relative light unit (RLU) values for the outer surfaces and forceps channels of the endoscopes, and a satisfaction survey was conducted with nurses who used the endoscope transport trolleys/carts and the endoscope cleaning staff.Results: The ATP values for the outer surfaces and forceps channels of the endoscopes in the experimental group were 10.0 (6.0, 17.0) RLU and 7.0 (4.0, 11.0) RLU, respectively, lower than 33.5 (9.3, 77.0) RLU for outer surfaces and 14.0 (5.0, 39.8) RLU for forceps channels in the control group. The pass rates for cleaning quality of the outer surfaces and channels of the endoscopes in the experimental group were 98.9% and 100%, respectively, higher than 88.6% for outer surfaces and 93.2% for channels in the control group (P < 0.05). The satisfaction scores of the nurses who used the multifunctional endoscope transport carts and the endoscope cleaning staff in the experimental group were 39.7± 1.87 and 18.45± 1.41, respectively, higher than 19.83± 2.08 for nurses and 9.08± 1.71 for cleaning staff in the control group (P < 0.05).Conclusion: The application of multifunctional endoscope transport carts in bedside endoscopy in ICU patients could improve the quality of endoscope cleaning.Keywords: transport carts, intensive care unit, bedside endoscopy, adenosine triphosphate test